First Record Of Cherry Leaf Spot Caused By Cylindrosporium Padi (P. Karst.) From India (Applied Biological Research, 2014)
Cherry (Prunus avium L.), an important stone fruit of temperate zone, is grown on an area of 3,728  ha in Jammu & Kashmir State with an annual production of 11,122 metric tonnes (Anonymous,  2012). In June-July 2013, typical leaf spot symptoms, quite different from those caused by  Cercospora and Stigmina pathogens, were noticed on cherry leaves from Bandipora, Baramulla and  Srinagar districts in Kashmir. The disease symptoms initially manifested as small circular purple
Keywords: First Record; Cylindrosporium